1998
DOI: 10.1002/(sici)1097-0142(19981215)83:12<2521::aid-cncr17>3.3.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative CA 15‐3 concentrations predict outcome of patients with breast carcinoma

Abstract: Preoperative serum concentrations of CA 15-3 appear to have a significant relation to outcome in patients with early breast carcinoma and may have a role in the rational selection of patients for appropriate adjuvant treatments. To the authors' knowledge, CA 15-3 thus is one of the first circulating markers shown to be an independent prognostic indicator in patients with breast carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
22
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 16 publications
(17 reference statements)
2
22
1
Order By: Relevance
“…As we determined both markers, CEA and CA 15-3, it is difficult to compare our study with the two other relevant studies of Gion and Shering (Gion et al, 1991;Shering et al, 1998). Although Gion found, in accordance to us, that pre-operative serum levels of CA 15-3 had no prognostic relevance in multivariate analysis, the number of patients and the unknown number of relapse and death from disease is probably too small to give reliable results.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…As we determined both markers, CEA and CA 15-3, it is difficult to compare our study with the two other relevant studies of Gion and Shering (Gion et al, 1991;Shering et al, 1998). Although Gion found, in accordance to us, that pre-operative serum levels of CA 15-3 had no prognostic relevance in multivariate analysis, the number of patients and the unknown number of relapse and death from disease is probably too small to give reliable results.…”
Section: Discussionmentioning
confidence: 54%
“…In contrast Shering et al (1998) reported on a high number of patients and found a prognostic relevance for pre-operative CA 15-3 values. The prognostic relevance of a single factor in multivariate analysis depends on which and how other factors are included in the model.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Much less has been written about the prognostic value of tumour markers. Correlations between raised preoperative levels of CA15.3 and CEA with poorer outcome have been reported (Molina et al, 1998;Shering et al, 1998;Ebeling et al, 1999;McLaughlin et al, 2000;Canizares et al, 2001). To our knowledge, the prognostic significance of an elevated CA15.3 and CEA in patients presenting with bone metastases has not been previously described.…”
Section: Discussionmentioning
confidence: 86%